2017
DOI: 10.1080/17470218.2016.1164733
|View full text |Cite
|
Sign up to set email alerts
|

Semantic and phonological influences on visual word learning in a transparent language

Abstract: Orthographic representations of words are indispensable for reading fluency. The ways in which these representations are developed and their resistance to decay are hotly debated topics. The aim of this study was to investigate the influence of semantic and phonological representations on the formation of orthographic representations in a transparent orthography. In order to achieve this objective, an experiment with three conditions was carried out. In the first condition, a group of university students were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 48 publications
2
9
2
Order By: Relevance
“…Our results are also similar to those of a Spanish study conducted with adults (Suárez‐Coalla & Cuetos, ), which used a similar training methodology. They also found that semantic and phonological training facilitated the formation of orthographic representations of new words among Spanish adults.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results are also similar to those of a Spanish study conducted with adults (Suárez‐Coalla & Cuetos, ), which used a similar training methodology. They also found that semantic and phonological training facilitated the formation of orthographic representations of new words among Spanish adults.…”
Section: Discussionsupporting
confidence: 89%
“…To meet this objective, we conducted an experiment that involved giving the children a task of repeatedly reading aloud unknown words under three different conditions: with prior semantic and phonological training (i.e., hearing and repeating the pronunciation while seeing a picture corresponding to the meaning), with only prior phonological training (i.e., only repeating the phonological form) and without training. Orthographic learning was measured using the reduction in the length effect of RTs after six times of repeated reading, a methodology successfully used in previous studies (Kwok & Ellis, ; Suárez‐Coalla et al, ; Suárez‐Coalla, Avdyli, & Cuetos, ; Suárez‐Coalla & Cuetos, ; Suárez‐Coalla, Ramos, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We take this reflect the creation of larger scale orthographic and phonological representations for the novel items, representations that are able to convert trained nonwords from written to spoken form on a more parallel, holistic basis (cf. Coltheart et al, 2001;Kwok & Ellis, 2014Maloney et al, 2009;Suárez-Coalla & Cuetos, 2016;Weekes, 1997).…”
Section: Word Learning and The Durability Of New Lexical Representationsmentioning
confidence: 99%
“…Furthermore, they could be related to studies in Spanish that have shown that the reading strategies vary throughout development (e.g., Ardila & Cuetos, 2016; Cuetos & Suárez-Coalla, 2009). In Spanish adults, Suárez-Coalla and Cuetos (2016) showed that the readers benefited from both semantic and phonological cues for the formation of new orthographic representations.…”
Section: Discussionmentioning
confidence: 99%